“I dreamed I died” War and death on adolescents’ dreams who are subjected to socio-educational measures - Bayer, Bruna; Gurski, Rose (Clinical Styles. The Journal on the vicissitudes of childhood, 2023)
This article presents the reflections about the experience with Wheels of Dreams (Rodas dos Sonhos), a clinical-political device, developed around the research-intervention work of NUPPEC, with teenagers who are on depravation of liberty on detention centers for juvenile offenders. We emphasize the theme of war and death present in the narration of the dreams of teenagers in association with the desire for death that Brazilian society directed to these young people. We explicit the violent context of Brazilian youth in social vulnerability situation, sustained by the logic of capitalist and neoliberal discourses. We share some oneiric narratives, in which we problematized the effects of death policies and violence towards the country’s young black and poor people. We understand that the Wheels of Dreams offer a mode of resistance in the face of deadly discourses directed at these young people.